2018 44th Euromicro Conference on Software Engineering and Advanced Applications (SEAA) 2018
DOI: 10.1109/seaa.2018.00070
|View full text |Cite
|
Sign up to set email alerts
|

An Automated Approach for Classifying Reverse-Engineered and Forward-Engineered UML Class Diagrams

Abstract: Context: In modern software development, software modeling is considered to be an essential part of the software architecture and design activities. The Unified Modeling Language (UML) has become the de facto standard for software modeling in industry. Surprisingly, there are only a few empirical studies on the practices and impacts of UML modeling in software development. This is mainly due to the lack of empirical data on real-life software systems that use UML modeling. Objective: This PhD thesis contribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 147 publications
(319 reference statements)
0
7
0
Order By: Relevance
“…Despite its effectiveness, this method to image classification consumes 5.84 seconds per image, which can be problematic when using it with big datasets. Mohd Hafeez Osman et al showed that reverse-engineered and forward-engineered UML class diagrams can be classified by using machine learning [26]. Ahmed and Huang also applied machine learning to classify role stereotypes of UML class diagrams in order to quickly get the knowledge about role stereotypes for developers [27].…”
Section: Related Workmentioning
confidence: 99%
“…Despite its effectiveness, this method to image classification consumes 5.84 seconds per image, which can be problematic when using it with big datasets. Mohd Hafeez Osman et al showed that reverse-engineered and forward-engineered UML class diagrams can be classified by using machine learning [26]. Ahmed and Huang also applied machine learning to classify role stereotypes of UML class diagrams in order to quickly get the knowledge about role stereotypes for developers [27].…”
Section: Related Workmentioning
confidence: 99%
“…As many empirical studies in Software Engineering are done on open source projects, the automated extraction and analysis of large sets of project data become possible. For researching the effects of UML modeling in open source projects, we need a way to automatically determine the type of UML use in a project [15].…”
Section: Motivationmentioning
confidence: 99%
“…The task of classifying UML class diagrams between manually created (for forward engineering) and reverse engineered is tackled in [41]. Several classification and features are tried, over a dataset of 999 UML models.…”
Section: Applicationsmentioning
confidence: 99%